Complex Horticultural Quality Traits in Broccoli Are Illuminated by Evaluation of the Immortal BolTBDH Mapping Population - Stansell, Zachary; Farnham, Mark; Björkman, Thomas (Frontiers in Plant Science, 2019)
Improving horticultural quality in regionally adapted broccoli (Brassica oleracea var. italica) and other B. oleracea crops is challenging due to complex genetic control of traits affecting morphology, development, and yield. Mapping horticultural quality traits to genomic loci is an essential step in these improvement efforts. Understanding the mechanisms underlying horticultural quality enables multi-trait marker-assisted selection for improved, resilient, and regionally adapted B. oleracea germplasm. The publicly-available biparental double-haploid BolTBDH mapping population (Chinese kale x broccoli; N = 175) was evaluated for 25 horticultural traits in six trait classes (architecture, biomass, phenology, leaf morphology, floral morphology, and head quality) by multiple quantitative trait loci mapping using 1881 genotype-by-sequencing derived single nucleotide polymorphisms. The physical locations of 56 single and 41 epistatic QTL were identified. Four head quality QTL (OQ C03@57.0, OQ C04@33.3, OQ CC08@25.5, and OQ C09@49.7) explain a cumulative 81.9% of phenotypic variance in the broccoli heading phenotype, contain the FLOWERING LOCUS C (FLC) homologs Bo9g173400 and Bo9g173370, and exhibit epistatic effects. Three key genomic hotspots associated with pleiotropic control of the broccoli heading phenotype were identified. One phenology hotspot reduces days to flowering by 7.0 days and inlcudes an additional FLC homolog Bo3g024250 that does not exhibit epistatic effects with the three horticultural quality hotspots. Strong candidates for other horticultural traits were identified: BoLMI1 (Bo3g002560) associated with serrated leaf margins and leaf apex shape, BoCCD4 (Bo3g158650) implicated in flower 28 color, and BoAP2 (Bo1g004960) implicated in the hooked sepal horticultural trait. The BolTBDH population provides a framework for B. oleracea improvement by targeting key genomic loci contributing to high horticultural quality broccoli and enabling de novo mapping of currently unexplored traits.